(untitled) (Journal of Global Arts Studies, 2025)
Background: Worsening marine ecological degradation highlights the urgency of enhancing children’s marine conservation awareness. Traditional picture books, constrained by linear narration and passive reading, are insufficient for conveying complex environmental issues, while Augmented Reality (AR) technology enables immersive and interactive learning for environmental education. Objective: This study explores how AR-enhanced picture book design improves children’s engagement with marine conservation themes and proposes an interactive design framework for AR digital picture books. Methods: A print-AR dual-medium model was adopted, with first-person baby sea turtle narration contrasting healthy and crisis marine scenarios. Multimodal elements and task-based interaction were integrated; AR prototypes were built via Kivicube image recognition and refined through iterative usability testing. Results: The AR picture book converts static ecological information into vivid, participatory experiences, boosting immersion, attention and emotional resonance. It improves children’s understanding of marine issues and is applicable to parent–child reading and public education. Conclusion: AR-based picture books provide an effective environmental education approach via immersive storytelling and intuitive interaction, offering practical design strategies for marine conservation communication.